A case study on Amyand hernia: The uncommon form of hernia - Fatima Khurshid; Muzzamal Hussain; Shahzeb Chaudhry; Khadija Malik; Sabahat Touseef (World Scientific Publishing, 2023)
An Amyand hernia is a rare type of inguinal hernia, accounting for less than 1% of all inguinal hernias, in which the appendix is found within the hernia sac, and is more common in males. The treatment of Amyand hernias is surgical, and the type of surgery depends on the extent of the hernia and the condition of the appendix. In this report, we will discuss the case of a 65-year-old male patient who presented with a reducible right inguinal swelling. During surgery, the hernia was found to contain an inflamed appendix, which was removed. The patient was treated with appendectomy along with mesh repair with postoperative antibiotic course. We discuss the diagnosis and management of Amyand hernias, also highlight the need for prompt diagnosis and treatment to prevent serious complications. We conclude that although Amyand hernias are rare, they should be considered in the differential diagnosis of inguinal hernias, especially in male patients.